Different Madrasah, but the Same Stories: Academic and Non-Academic Challenges Encountered by Teachers in Teaching A Foreign Language - NUNUNG FAJARYANI; MASBIROROTNI MASBIROROTNI; NURAINI NURAINI; NAFRIAL NAFRIAL; NOPIANTI NOPIANTI (Ta'dib: Jurnal Pendidikan Islam, 2018)
This qualitative case study aimed to investigate English teachers’ challenges in teaching English at Madrasah Tsanawiyah. It also aimed to find out the English teachers’ effort to anticipate the challenges factors in teaching English. In this research, the researchers puposefully selected all the English teachers at Madrasah Tsanawiyah Jambi Timur and Madrasah Dharma Wanita as the participants. Data were collected through a demographic questionnaire and the interviews. The demographic data were analyzed descriptively. The interviews data were analyzed using within-case and cross-case displays and analyses. The result proved that there were four major themes including academic challengeing factors (students’ demotivation and low students’ basic English ability), non academic challengeing factors (lack of facilities, crowded classroom, socio economic level, and school management), teachers’ effort, and leader’s support.